2017
DOI: 10.1080/14767058.2017.1410789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gly71Arg mutation in UGT1A1 gene on neonatal hyperbilirubinemia: a systematic review and meta-analysis

Abstract: This meta-analysis confirms that UGT1A1 Gly71Arg polymorphism significantly increases the risk of neonatal hyperbilirubinemia in Asian population, but results from the Caucasians were conflicting and further well-designed epidemiological studies are, therefore, required to more adequately assess this correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…(TA) 7 TAA/A(TA) 7 TAA, is the main genetic cause in Asians. 73,74 The results of our review confirmed these findings (except for Indonesian, 14,40 Malaysian, 52 and Saudi 21 populations). Moreover, the TA 7 repeat variant of UGT1A1 appears to exert a protective effect on hyperbilirubinemia development in Chinese, 28 Japanese, 48,75 and Taiwanese 57,67 neonates fed breast milk.…”
Section: Neonatal Hyperbilirubinemiasupporting
confidence: 84%
“…(TA) 7 TAA/A(TA) 7 TAA, is the main genetic cause in Asians. 73,74 The results of our review confirmed these findings (except for Indonesian, 14,40 Malaysian, 52 and Saudi 21 populations). Moreover, the TA 7 repeat variant of UGT1A1 appears to exert a protective effect on hyperbilirubinemia development in Chinese, 28 Japanese, 48,75 and Taiwanese 57,67 neonates fed breast milk.…”
Section: Neonatal Hyperbilirubinemiasupporting
confidence: 84%
“…A variant of the TATAA box that has an additional TA insertion (A(TA)7TAA) ( UGT1A1 * 28 ) was found to be associated with GS and CNs, with the mutation being found most frequently in Caucasian and African populations (1, 13, 1619). In the East Asian population, however, UGT1A1 * 6 (211G > A) is the most prevalent single nucleotide polymorphism (SNP) (16, 17, 20, 21). This variant leads to an amino acid substitution of glycine-71 to arginine.…”
Section: Introductionmentioning
confidence: 99%
“…Our results reveal that neonatal hyperbilirubinemia in Taiwanese is related to 211 G > A variant in the UGT1A1 gene, while such a variant is very rare in Caucasians. 6 Therefore, we recommend that information about neonatal hyperbilirubinemia and breastfeeding hyperbilirubinemia could be incorporated into prenatal education for mothers who intend to breastfeed, as other Taiwanese authors reported recently. 26 Furthermore, we agree that further study may be needed to target women who stopped breastfeeding because of breastfeeding hyperbilirubinemia specifically.…”
Section: Discussionmentioning
confidence: 86%